Maintien du potentiel adaptatif chez les plantes domestiquées à propagation clonale - Doyle McKey; Marianne Elias; Benoît Pujol; Anne Duputié; Marc Delêtre; Delphine Renard (Revue d'ethnoécologie)
We studied how Amerindian cultivators of manioc in Amazonia simultaneously maintain the genetic diversity and the agronomic performance of their populations of this plant. A shrub domesticated in Amazonia probably over 7000 years ago, manioc is today the staple food for over a billion people throughout the tropical world. It is propagated by farmers by stem cuttings : a small section of stem is cut from a mature plant and directly planted in the ground. This amounts to cloning. Cloning is the only efficient way to “capture” and multiply initially rare favourable phenotypes in habitually outcrossed plants such as manioc. However, practiced to the exclusion of sexual reproduction, clonal propagation can lead to erosion of genetic diversity of crop populations, and thus to the loss of the plant’s potential to adapt to stresses such as droughts or the advent of a new pathogen. We have shown that Amerindian cultivators regularly incorporate “volunteer” plants issued from spontaneously produced seedlings into their stocks of clones. These plants are recruited from a bank of dormant seeds in the soil. Seeds of manioc can remain dormant in soil for up to several decades, germinating when a disturbance creates the open conditions favourable for establishment. Each volunteer plant from seed is a new recombinant genotype, and the incorporation of these plants by farmers in their stocks of clones maintains genetic diversity in the population. However, the mating system in manioc populations in Amerindian fields is highly inbred, and agronomic performance of inbred individuals is very low. By highly selective incorporation of volunteer plants – via processes that combine both natural and artificial selection – Amerindian cultivators are able to maintain simultaneously genetic diversity and agronomic performance of their manioc populations, combining sexual reproduction and clonal propagation in a way that reaps the benefits of each mode of reproduction while minimizing their respective disadvantages. In regions where manioc has been introduced since the “discovery” of America by Europeans, the technical knowledge of Amerindian cultivators about the use of products of manioc’s sexual reproduction has not been introduced along with the plant. We examine the potential consequences of the slow and patchy reinvention of this knowledge for manioc’s continued contribution to food security.